Frequent detection of human cytomegalovirus in neuroblastoma: A novel therapeutic target?. Issue 10 (13th July 2013) - Wolmer‐Solberg, Nina; Baryawno, Ninib; Rahbar, Afsar; Fuchs, Dieter; Odeberg, Jenny; Taher, Chato; Wilhelmi, Vanessa; Milosevic, Jelena; Mohammad, Abdul‐Aleem; Martinsson, Tommy; Sveinbjörnsson, Baldur; Johnsen, John Inge; et al.
<x xml:space="preserve">Abstract</x> Neuroblastoma is the most common and deadly tumor of childhood, where new therapy options for patients with high‐risk disease are highly warranted. Human cytomegalovirus (HCMV) is prevalent in the human population and has recently been implicated in different cancer forms where it may provide mechanisms for oncogenic transformation, oncomodulation and tumor cell immune evasion. Here we show that the majority of primary neuroblastomas and neuroblastoma cell lines are infected with HCMV. Our analysis show that HCMV immediate‐early protein was expressed in 100% of 36 primary neuroblastoma samples, and HCMV late protein was expressed in 92%. However, no infectious virus was detected in primary neuroblastoma tissue extracts. Remarkably, all six human neuroblastoma cell lines investigated contained CMV DNA and expressed HCMV proteins. HCMV proteins were expressed in neuroblastoma cells expressing the proposed stem cell markers CD133 and CD44. When engrafted into NMRI nu/nu mice, human neuroblastoma cells expressed HCMV DNA, RNA and proteins but did not produce infectious virus. The HCMV‐specific antiviral drug valganciclovir significantly reduced viral protein expression and cell growth both in vitro and in vivo. These findings indicate that HCMV is important for the pathogenesis of neuroblastoma and that anti‐viral therapy may be a novel adjuvant treatment option for children with neuroblastoma.